Software implementation of neural network technologies for automated textual information classification - Yakovenko, V. O.; Ulianovska, Yu. V.; Kaliaka, O. O. (Systems and Technologies, 2018)
The results of the analysis of the state of highways suitable for the organiza-tion of high-speed traffic on the route Kyiv-Dnipro are presented, and the main directions of its implementation are identified. The calculations of permissible technical parameters of the movement of vehicles on certain routes. It is shown that the proportion of heavy and large-sized vehicles grows in the transport flows, which leads to the rapid destruction of roads and bridges, which are designed for much smaller volumes and loads. For the introduction of high-speed traffic pro-posed measures to improve the technical level of existing roads. The necessity of intensification of the modernization and repair of roads in Ukraine based on the use of modern technologies, which will create the necessary conditions for the introduction of high-speed road transport.